Sleep disorders as a prospective intervention target to prevent drug relapse - Sun, Chao; Wang, Xiaojun; Huang, Xuetong; Shao, Yongcong; Ling, Anna; Qi, Huanhuan; Zhang, Zhuolin (Frontiers in Public Health, 2023)
Objective The high rate of relapse has become the primary obstacle of drug rehabilitation. In this study, we explored the relationship between sleep disorders and relapse inclination in substance users, as well as the potential mediating mechanisms and corresponding interventions. Methods A total of 392 male substance users were recruited to complete the questionnaires on sleep disorders, quality of life and relapse inclination. On account of this, 60 participants with sleep disorders were randomly screened and allocated to the intervention and control groups. The former received 12 weeks of Health Qigong aimed at treating sleep disorders, whereas the latter performed their regular production work. Results Sleep disorders had a positive effect on relapse inclination, quality of life was a potential mediator of this relationship, and 12-week Health Qigong designed to treat sleep disorders improved not only their sleep quality but also their overall quality of life, which in turn reduce the tendency to relapse. Conclusion Current research not only explores the high-risk factors influencing relapse, but also develops customized intervention strategies, which have theoretical and practical implications for decreasing relapse and increasing abstinence.